IMPACT OF PUBLIC PROCUREMENT ON THE DEVELOPMENT OF A COMPETITIVE ENVIRONMENT IN THE ECONOMY OF UKRAINE - DEMIANENKO, Tetiana; YEVCHENKO, Veronika (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the impact of the public procurement system on the formation and development of a competitive environment in the economy of Ukraine under conditions of economic transformation, European integration, and martial law. The relevance of the study is determined by the significant role of public procurement in aggregate demand, the large volume of budgetary resources redistributed through procurement procedures, and the need to ensure transparency, efficiency, and fair competition in markets for goods, works, and services.The study substantiates the importance of public procurement as an instrument of state economic policy that directly influences the level of competition, market behavior of business entities, and the quality of the economic environment. The functioning of the Prozorro electronic procurement system is analyzed, and its role in increasing transparency, reducing corruption risks, and expanding access for small and medium-sized enterprises is highlighted. Positive effects of competitive procurement mechanisms are identified, including an increase in the number of bidders, intensification of price competition, and savings of public funds.At the same time, the research identifies key challenges that hinder the development of a fully competitive environment, such as unfair practices by market participants, discriminatory tender requirements, risks of cartel collusion, and reduced transparency under martial law conditions. The necessity of further improvement of institutional control mechanisms, strengthening antimonopoly policy, and enhancing the professional capacity of contracting authorities is substantiated.The article concludes that an efficient and competitive public procurement system is a crucial prerequisite for the sustainable development of the national economy, rational use of public finances, and increased trust of businesses in public institutions.
Keywords: public procurement; competition; competitive environment; public policy; Prozorro; transparency; open data; economic development